The autoimmune regulator AIRE in thymoma biology: autoimmunity and beyond - Marx, Alexander; Hohenberger, Peter; Hoffmann, Hans; Pfannschmidt, Joachim; Schnabel, Philipp Albert; Hofmann, Hans-Stefan; Wiebe, Karsten; Schalke, Berthold; Nix, Wilfred; Gold, Ralf; Willcox, Nick; Peterson, Pärt; et al. (Journal of thoracic oncology, 2010)
Thymomas are tumors of thymic epithelial cells. They associate more often than any other human tumors with various autoimmune diseases; myasthenia gravis is the commonest, occurring in 10-50% of thymoma patients, depending on the World Health Organization-defined histologic subtype. Most thymomas generate many polyclonal maturing T lymphocytes but in disorganized microenvironments Failure to induce self-tolerance may be a key factor leading to the export of potentially autoreactive CD4+ progeny, thus predisposing to autoimmune diseases. Normally, the master Autoimmune Regulator promotes expression of peripheral tissue-restricted antigens such as insulin by medullary thymic epithelial cells and induction of tolerance to them. The failure of ∼95% of thymomas to express autoimmune regulator is another feature potentially contributing to autoimmunity.
Online veröffentlicht am 20. November 2015
Gesehen am 23.05.2023